ISLAM AND MUSIC - Qadamboy Rahimov (American Journals, 2024)
Much has been done to develop the knowledge of music from ancient times. Many work was done by the composers and musicians of that era. Mature philosophers of his day published various brochures on the science of music, developed Uzbek music, and the article discusses the impact and educational significance of traditional Uzbek songs on the human spirit.
Keywords: Rage, song, poetry, yor – yor, folklore, Ar·ta·xerxʹes, musical instruments, singer, musician, writing, characters, harp system.